Depression during pregnancy and the postpartum period in adolescent and adult Portuguese mothers - Figueiredo, Bárbara (2007)
Objective: To study prevalence as well as risk factors for pregnancy and postpartum depression in a sample of adolescent and adult Portuguese mothers. Methods: The Edinburgh Postnatal Depression Scale (EPDS) was administered to 108 (54 adult and 54 adolescent) Portuguese women at 24–36 weeks of pregnancy and at 2–3 months postpartum. Results: Rates for EPDS > 12 are high during the 3rd trimester of pregnancy (18.5%) and at 2–3 months postpartum (17.6%), and not significantly different between these two periods; more than 1=4of the sample (27.8%) had an EPDS > 12 before or after delivery. Adolescent mothers presented more depressive symptoms as well as more EPDS > 12 than adult mothers, both in pregnancy (25.9% versus 11.1%) and at 2–3 months postpartum (25.9% versus 9.3%); moreover, when considering other socio-demographics, adolescent mothers were still at risk for depressive symptoms during pregnancy as well as for postpartum depression. Women depressed in pregnancy, and ones who are under 18 years old and who live with the partner, were at risk for postpartum EPDS > 12. Conclusion: Adolescent mothers seem particularly at risk for depression during pregnancy and the postpartum period, therefore, just like the women who are depressed during pregnancy, they should be better targeted in preventive and intervention measures.